Metode Forward Chaining Pada Sistem Pakar Diagnosa Gangguan Mesin Sepeda Motor Vespa-2-Tak - Ahtian, Muzaid; Sari, Rafika (Journal of Students‘ Research in Computer Science, 2022)
Motorcycles are a means of transportation that have become a primary need for most urban communities in Indonesia. Apart from being a necessity, it is not uncommon for some people to make motorbikes a hobby. This hobby of motorbikes then raises the need for knowledge of vehicle maintenance. In this study, several problems with vehicles of Vespa-2-Tak will be reviewed that require knowledge for maintenance. The maintenance of existing vehicles in most Vespa-2-Tak vehicle repair shops is still manual. This study initiated the idea to try to implement an expert system application using the forward chaining method to diagnose motorcycle Vespa-2-tak problems. This expert system is implemented in a web-based software application with a waterfall development model. Testing with the black-box testing method obtained good results. Thus, this expert system can help Vespa-2-Tak motorcycle users to find out the disturbance or damage to their vehicle and alternative solutions without having to come directly to the bike shop.